Flow investigation in a centrifugal pump - Abdul Razak Juma'at (2012)
A computational fluid dynamic simulation was conducted using ANSYS FLUENT v 13.0 to investigate the flow in a centrifugal blood pump. The modelling process was conducted using the design program GAMBIT. 4 different models were designed, each having different clearance gap sizes; 0.2mm, 0.3mm, 0.4mm and 0.5mm gap. During the simulation, the leakage flow, pressure and velocity distribution was analysed with the boundary conditions of 2000 rpm rotational impeller speed and inlet flow rate ranging from 1 litre per minute to 7 litres per minute. A separate simulation was done for each of the 4 pumps with the differing gap sizes as well.